Pathway retrofitting yields insights into the biosynthesis of anthraquinone-fused enediynes - Ma, Guang-Lei (2022)
Anthraquinone-fused enediynes (AQEs) are renowned for their distinctive molecular architecture, reactive enediyne warhead, and potent anticancer activity. Although the first members of AQEs, i.e., dynemicins, were discovered three decades ago, how their nitrogen-containing carbon skeleton is synthesized by microbial producers remains largely a mystery. In this study, we showed that the recently discovered sungeidine pathway is a “degenerative” AQE pathway that contains upstream enzymes for AQE biosynthesis. Retrofitting the sungeidine pathway with genes from the dynemicin pathway not only restored the biosynthesis of the AQE skeleton but also produced a series of novel compounds likely as the cycloaromatized derivatives of chemically unstable biosynthetic intermediates. The results suggest a cascade of highly surprising biosynthetic steps leading to the formation of the anthraquinone moiety, the hallmark C8−C9 linkage via alkyl−aryl cross-coupling, and the characteristic epoxide functionality. The findings provide unprecedented insights into the biosynthesis of AQEs and pave the way for examining these intriguing biosynthetic enzymes.